The language of hookups a conversation and self-presentation analysis of Tinder chats - Jalagat, Joseph Ryann J.; Yapo, Jerry R. (2021)
Access online through this link: https://www.plarideljournal.org/article/the-language-of-hookups-a-conversation-and-self-presentation-analysis-of-tinder-chats
Keywords: Online dating mobile apps; Tinder (Web resource); Dating (Social custom); Human sexuality